2018
DOI: 10.18203/2394-6040.ijcmph20183979
|View full text |Cite
|
Sign up to set email alerts
|

Does emotional intelligence upon interaction with perceived stress, moderate burnout among resident doctors? A study from West Bengal, India

Abstract: Background: Burnout as a result of perceived stress is a jeopardizing condition for a medical graduate during the years of acquiring proficiency. Emotional intelligence (EI) is a coping strategy to handle vocational stress. The objectives of the study were to assess the effects of various predictors on resident doctors’ burnout and moderation effects of TEI by interaction with perceived stress.Methods: A descriptive cross-sectional study was conducted from February to April 2016 among 61 postgraduate trainees … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
2
1
Order By: Relevance
“…Working ≥1 long shift per month and ≥4 long shifts per week were also associated with high EE and overall burnout, but the risk conferred by other shift frequencies (ie, >0 to <2, 2 to <4 long shifts per week) was less consistent for these aspects of burnout. Working ≥48 hours per week was associated with reduced odds of low PA in police, which contrasts research in physicians using a similar definition of weekly work hours,22 as well as a prior study in UK police that defined long work weeks using a slightly higher threshold (≥49 hours per week) 27. Long work weeks and night shifts (1–4 per week) were the only shift characteristics in this study associated with reduced odds of low PA.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…Working ≥1 long shift per month and ≥4 long shifts per week were also associated with high EE and overall burnout, but the risk conferred by other shift frequencies (ie, >0 to <2, 2 to <4 long shifts per week) was less consistent for these aspects of burnout. Working ≥48 hours per week was associated with reduced odds of low PA in police, which contrasts research in physicians using a similar definition of weekly work hours,22 as well as a prior study in UK police that defined long work weeks using a slightly higher threshold (≥49 hours per week) 27. Long work weeks and night shifts (1–4 per week) were the only shift characteristics in this study associated with reduced odds of low PA.…”
Section: Discussioncontrasting
confidence: 96%
“…Total work hours across the month were recorded using a validated questionnaire,20 with those recording ≥48 hours per week considered to be working long work weeks. This categorisation was based on prior benchmarking literature in the USA which defines long work weeks as 48 or more hours per week21 and research which has shown this cut-off to be associated with burnout 22. Participants also recorded if they completed mandatory and/or voluntary overtime over the last 4 weeks and the total number of hours they slept each week for the previous 4 weeks.…”
Section: Methodsmentioning
confidence: 99%
“…experience interactions with "difficult patients" within their role as learners and within the clinical learning environment (Swami, Mathur, and Pushp, 2013). Most of the available literature have focused on patient and physicians characteristics during difficult encounters but there is less written about the increase prevalence of this situation in the young doctors, outcomes of difficult encounters and how physicians actually manage difficult patients Instead, management advice is given anecdotally or from an educational or psychological perspective without any scientific evidence generally in the essays form usually based upon the expert opinion or personal experience of author.…”
Section: Introductionmentioning
confidence: 99%